The importance of evidence-based and transparent communication to get trust towards vaccination programs - Lopalco, Pier Luigi (Brazilian Journal of Sexually Transmitted Diseases, 2013)
Vaccination programs represent a very effective (and costeffective) tool for public health. Benefits of vaccination are witnessed by many success stories: smallpox has been eradicated; fight against polio is coming to an end; measles and rubella have been eliminated from the Americas and dramatically reduced all over the world; deadly diseases like tetanus and diphtheria have virtually disappeared in large areas of the world. [...]